2013
DOI: 10.1111/acer.12070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacterial Pneumonia on Lung Simian Immunodeficiency Virus (SIV) Replication in Alcohol Consuming SIV‐Infected Rhesus Macaques

Abstract: Background Opportunistic infections in HIV-infected persons have been shown to increase the rate of HIV replication. In populations where prophylaxis against Pneumocystis pneumonia is utilized, bacterial pneumonia is now the leading cause of lower respiratory tract infection in HIV+ patients. Our prior studies have shown that chronic alcohol consumption in simian demarcated immunodeficiency virus (SIV) infected rhesus macaques increases plasma viral load set point and accelerates progression to end-stage AIDS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 57 publications
2
19
0
Order By: Relevance
“…The increase in viral replication following CBA could lead to a decreased capacity to control viral reactivation during opportunistic infections. In support of this hypothesis, results from our studies show that S. pneumoniae inoculation results in prolonged viral replication in the infected lungs of CBA-administered SIV-infected macaques, as compared to that of SIV-infected controls (Nelson et al 2013). Increased localized HIV replication, particularly in alveolar macrophages and CD4 + cells, has been reported to increase viral mutations and promote viral escape from latent reservoirs (Nelson and Bagby 2011).…”
Section: Introductionsupporting
confidence: 70%
“…The increase in viral replication following CBA could lead to a decreased capacity to control viral reactivation during opportunistic infections. In support of this hypothesis, results from our studies show that S. pneumoniae inoculation results in prolonged viral replication in the infected lungs of CBA-administered SIV-infected macaques, as compared to that of SIV-infected controls (Nelson et al 2013). Increased localized HIV replication, particularly in alveolar macrophages and CD4 + cells, has been reported to increase viral mutations and promote viral escape from latent reservoirs (Nelson and Bagby 2011).…”
Section: Introductionsupporting
confidence: 70%
“…ART was continued throughout the study period. At four and a half months of SIV infection, animals were inoculated with 2 ϫ 10 6 CFU of S. pneumoniae, serotype 19F (ATCC 6319), into a subsegment of the lower lobe of the right lung using a pediatric bronchoscope as previously described (14). Monkeys underwent bronchoscopies and bronchial brushings prepneumonia and day 1 postpneumonia.…”
Section: Methodsmentioning
confidence: 99%
“…As the lung epithelium is a major site of chemokine production during bacterial pneumonia (12), we examined the effect of ethanol on gene expression in the airway epithelium during experimental S. pneumoniae infection in a nonhuman primate model of ethanol consumption and pneumococcal infection (13,14). We analyzed bronchial brush samples for gene expression using RNA sequencing and determined that ethanol consumption was associated with downregulation of IL-17 inducible genes in the bronchial epithelium 24 h postinfection.…”
Section: Billion In 2006 (3)mentioning
confidence: 99%
“…Opportunistic infections, such as pneumonia, can increase viral replication thereby accelerating progression to AIDS. Our studies [30] have shown that direct intrapulmonary infection with S. pneumoniae leads to prolonged viral replication in infected lungs of SIV-infected alcohol-fed animals as compared to that of SIV-infected controls. The most likely site of viral replication is the alveolar macrophage [31].…”
Section: Alcohol-mediated Immunomodulation and Its Impact On Hiv Diseasementioning
confidence: 99%